Pelatihan Dan Pengembangan Resep Produk Minuman Jeruk Instan Guna Meningkatkan Perekonomian Masyarakat - Nugraha, Dhanang Prawira; Rollando, Rollando; Monica, Eva; Aziz, Nur; Susanto, F.X Haryanto (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Kucur Village is a tangerine producer in Malang Regency. However, people still sell it in fresh fruit form; besides that, the pest of fruit flies is also a scourge for farmers, and the absorption capacity in the market for fresh fruit is still relatively lower than the products produced. Processing oranges into secondary products can be a solution for farmers by processing tangerines. Ma Chung University's service aims to develop recipes for making instant powder drinks from tangerines to increase the tangerines' economic value. The method used is recipe development in the laboratory, which is practised in Kucur Village to find which recipe is most suitable and produce products for sale. The results of this service and the Kucur village community produced a recipe suitable for sale as an instant powder drink. The recipe for this instant powder drink contains an infusion of lemongrass stems, ginger, bay leaves, and lime.